New Insights Into Diuretic Use to Treat Congestion in the ICU: Beyond Furosemide - Escudero, Victor Joaquin; Mercadal, Jordi; Molina-Andújar, Alícia; Piñeiro, Gaston J.; Cucchiari, David; Jacas, Adriana; Carramiñana, Albert; Poch, Esteban (Frontiers in Nephrology, 2022)
Diuretics are commonly used in critically ill patients with acute kidney injury (AKI) and fluid overload in intensive care units (ICU), furosemide being the diuretic of choice in more than 90% of the cases. Current evidence shows that other diuretics with distinct mechanisms of action could be used in patients with selected profiles with good results. From acetazolamide to tolvaptan, we will discuss recent studies and highlight how specific diuretic mechanisms could help to manage different ICU problems, such as loop-diuretic resistance, hypernatremia, hyponatremia or metabolic alkalosis. The current review tries to shed some light in the potential use of non-loop diuretics based on patient profile and give recommendations of loop-diuretic treatment performance focused on what the intensivist and critical care nephrologist need to know based on the latest evidence.